Ovotesticular disorders of sex development in FGF9 mouse models of human synostosis syndromes. (26th May 2020) - Bird, Anthony D; Croft, Brittany M; Harada, Masayo; Tang, Lingyun; Zhao, Liang; Ming, Zhenhua; Bagheri-Fam, Stefan; Koopman, Peter; Wang, Zhugang; Akita, Keiichi; Harley, Vincent R
Abstract: In mice, male sex determination depends on FGF9 signalling via FGFR2c in the bipotential gonads to maintain the expression of the key testis gene SOX9 . In humans, however, while FGFR2 mutations have been linked to 46, XY disorders of sex development (DSD), the role of FGF9 is unresolved. The only reported pathogenic mutations in human FGF9, FGF9 S99N and FGF9 R62G, are dominant and result in craniosynostosis (fusion of cranial sutures) or multiple synostoses (fusion of limb joints). Whether these synostosis-causing FGF9 mutations impact upon gonadal development and DSD etiology has not been explored. We therefore examined embryonic gonads in the well-characterized Fgf9 missense mouse mutants, Fgf9 S99N and Fgf9 N143T, which phenocopy the skeletal defects of FGF9 S99N and FGF9 R62G variants, respectively. XY Fgf9 S99N/S99N and XY Fgf9 N143T/N143T fetal mouse gonads showed severely disorganized testis cords and partial XY sex reversal at 12.5 days post coitum (dpc), suggesting loss of FGF9 function. By 15.5 dpc, testis development in both mutants had partly recovered. Mitotic analysis in vivo and in vitro suggested that the testicular phenotypes in these mutants arise in part through reduced proliferation of the gonadal supporting cells. These data raise the possibility that human FGF9 mutations causative for dominant skeletal conditions can also lead to loss of FGF9 function in the developing testis, at least in mice. Our data suggest that, in humans, testis development is largely tolerant of deleterious FGF9 mutations which lead to skeletal defects, thus offering an explanation as to why XY DSDs are rare in patients with pathogenic FGF9 variants.